2021
DOI: 10.1093/inthealth/ihab032
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diarrhoea risk and the combinations of drinking water sources in the Kathmandu Valley, Nepal

Abstract: In Nepal, the number of diarrhoea hospitalizations in all ages is seriously high. According to the World Health Organization, diarrheal diseases can be substantially prevented through safe drinking water sources. In the Kathmandu Valley, because of the shortage of piped water, local residents use alternative water sources, such as groundwater, jars and tanker water. However, these alternative water sources can be contaminated. This study aimed to clarify the relationship between diarrhoea risk and the combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Lastly, using untreated water was a risk factor (p > 0.001) in the study. This has been proven in previous studies (23)(24)(25)(26)(27), contaminated water collected in the shallow wells (n = 136; 35.2%), community borehole (n =227; 58.8%) and personal borehole (n = 13; 3.4%) were neither chlorinated nor boiled before use. There is a need for environmental health services to ensure preventive measures such as the provision of safe water and health education on how to clean water before use.…”
Section: Discussionmentioning
confidence: 70%
“…Lastly, using untreated water was a risk factor (p > 0.001) in the study. This has been proven in previous studies (23)(24)(25)(26)(27), contaminated water collected in the shallow wells (n = 136; 35.2%), community borehole (n =227; 58.8%) and personal borehole (n = 13; 3.4%) were neither chlorinated nor boiled before use. There is a need for environmental health services to ensure preventive measures such as the provision of safe water and health education on how to clean water before use.…”
Section: Discussionmentioning
confidence: 70%
“…Lastly, using untreated water was a risk factor (p > 0.001) in the study. This has been proven in previous studies [25][26][27][28][29], as contaminated water collected in shallow wells (n = 136; 35.2%), community boreholes (n = 227; 58.8%), and personal boreholes (n = 13; 3.4%) was neither chlorinated nor boiled before use. There is a need for environmental health services to ensure preventive measures such as the provision of safe water and health education on how to clean water before use.…”
Section: Discussionmentioning
confidence: 73%
“…Hence, in this study, we strongly advise global (all nations) and LIC to focus on water quality and waterborne disease. Many studies have demonstrated that inadequate clean water and sanitation facilities increase health problems, especially those related to skin and eyes, gastrointestinal illnesses, and malaria, responsible for deaths annually [86]. Furthermore, water supply and home sanitation are correlated with physical and mental health [87].…”
Section: Priority Keys In Water-related Sdgsmentioning
confidence: 99%
“…sponsible for deaths annually [86]. Furthermore, water supply and home sanitation are correlated with physical and mental health [87].…”
Section: Priority Keys In Water-related Sdgsmentioning
confidence: 99%